Government Policy, Small Agribusiness And Regional Development In The Province Of Sumatera Utara, Indonesia - Subhilhar, Subhilhar (2007)
The objective of this study is to evaluate the impact of government intervention on small agribusiness in Indonesia. Generally government intervention here takes the forms of policies, programmes and projects that support the productive development of small agribusiness. In Sumatera Utara (North Sumatra), the region under study, local government policies encourage and may develop small agribusiness.